2004
DOI: 10.2166/wh.2004.0017
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium and Giardia in swimming pools in the Netherlands

Abstract: The occurrence of Cryptosporidium and Giardia in indoor swimming pools in the Netherlands was studied at five locations. The backwash water from seven pool filters was analysed for the presence of Cryptosporidium oocysts and Giardia cysts for a period of 1 year. Of the 153 samples of filter backwash water analysed, 18 (11.8%) were found positive for either Cryptosporidium (4.6%), Giardia (5.9%) or both (1.3%). Oocysts and cysts were also detected in the water of one toddler pool and one learner pool. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
22
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
3
22
0
2
Order By: Relevance
“…(4). In the Netherlands, 7 pools sampled for >1 year had a prevalence of 5.9% for Giardia sp., 4.6% for Cryptosporidium spp., and 1.3% for both pathogens (5). In Italy, 1 study found 28.6% (2/7) of tested pools were positive for both Giardia sp.…”
mentioning
confidence: 93%
“…(4). In the Netherlands, 7 pools sampled for >1 year had a prevalence of 5.9% for Giardia sp., 4.6% for Cryptosporidium spp., and 1.3% for both pathogens (5). In Italy, 1 study found 28.6% (2/7) of tested pools were positive for both Giardia sp.…”
mentioning
confidence: 93%
“…Swimming pools are often association with outbreak of water borne infections. The infection agents recovered from swimming pool water include a variety of pathogens embracing bacteria, viruses, protozoa and fungi including trichophyton spp [5][6][7][8][9]. Although modern swimming pools have a re-circulating system so that water can be filtered and disinfected, effectively, relevant studies shows that neither hi-tech systems nor disinfectants can prevent that colonization of a pool water with hazardous pathogens [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Many parasites that are transmitted by the fecal–oral route have been found in water (Dowd et al, 1998), but probably Cryptosporidium and Giardia are the most common ones (Gardner et al, 2001; Rose et al, 1996, Rose et al, 2002). They have been reported in wastewater (Mayer and Palmer, 1996), superficial water (Horman et al, 2004) and streambeds (Searcy et al, 2006), indoor pools (Schets et al, 2004), and drinking water (Hashimoto et al, 2002), living freely or in biofilms. Cryptosporidium caused the largest outbreak (400,000 people ill) ever documented in the U.S. when a drinking water treatment plant in Milwaukee (WI) malfunctioned (Mac Kenzie et al 1994).…”
Section: Introductionmentioning
confidence: 99%